2016
DOI: 10.1016/j.jrras.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocessing of citrus waste peel for induced pectinase production by Aspergillus niger; its purification and characterization

Abstract: Agro-industrial residues are primarily composed of complex polysaccharides that strengthen microbial growth for the production of industrially important enzymes. Pectinases are one of the most widely disseminated enzymes in bacteria, fungi and plants. Czapeck media supplemented with orange waste peel as carbon source under submerged fermentation process Aspergillus niger presenting the preeminent enzymatic production. On partial optimization culture showed the maximum enzyme yield (117.1 ± 3.4 mM/mL/ min) at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(63 citation statements)
references
References 24 publications
(18 reference statements)
6
49
1
6
Order By: Relevance
“…The increase in the specific activity of polygalacturonase (2.8 UI/mg) and pectin lyase (0.14 UI/mg) after dialysis could be explained by a loss of undesired proteins which interfere with the activity of pectinases (Undenwobele et al, 2014). These two first steps of purification (ammonium sulphate precipitation and dialysis) of enzymes have already been reported by Ahmed et al, (2016) in the purification of vegetable pectinases. The last step in the purification (Isoelectric focusing) of the polygalacturonase and pectin lyase isolated from the papaya pericarp cv.…”
Section: Resultsmentioning
confidence: 81%
“…The increase in the specific activity of polygalacturonase (2.8 UI/mg) and pectin lyase (0.14 UI/mg) after dialysis could be explained by a loss of undesired proteins which interfere with the activity of pectinases (Undenwobele et al, 2014). These two first steps of purification (ammonium sulphate precipitation and dialysis) of enzymes have already been reported by Ahmed et al, (2016) in the purification of vegetable pectinases. The last step in the purification (Isoelectric focusing) of the polygalacturonase and pectin lyase isolated from the papaya pericarp cv.…”
Section: Resultsmentioning
confidence: 81%
“…Low concentration of substrate N . D N.D indicates that activity is not detected a Submerged fermentation was carried out using 20.0 g l −1 of substrates with pH 7.0 at 40°C for 48 h. The data presented are the mean values of three replicates with standard deviations than optimum is mostly insufficient to fulfill the energy demand of bacterial culture and to induce the bacterium for maximum enzyme synthesis (Ahmed et al 2015). The total carbohydrate content of sweet potato peel was also determined, and it was observed that sweet potato peel contains 0.0015/0.1 g total sugar content.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the volatile content of the feed marks the yield of the reaction; furthermore, if the ash content is high the yield of the treatment will decrease. For the orange peel, the initial ash percentage reported by Ahmed et al [14], was 7.34%; while the initial ash content for the CH is non-existent according to studies carried out by Bondesson [15].…”
Section: Study Of the Performance Of Products For The Different Thermmentioning
confidence: 99%